OPTIMALISASI PENGENDALIAN PERSEDIAAN PRODUK ORGANIK MENGGUNAKAN METODE MIN-MAX PADA PT. XYZ (RETAIL GROCERY) - Andhini Putri Widhiasari (2022)
PT. XYZ is a company engaged in the grocery retail sector focusing on organic and sustainable products. Organic products, which are products that do not use preservatives in their production process, are then sustainable, namely the materials used in purchasing organic products do not use plastic. Demand from consumers has increased greatly, of course during a pandemic, so it is often found in stores experiencing stockouts due to inventory control in determining maximum and minimum levels in warehouses without mathematical calculations. The purpose of this study is to optimize inventory control by calculating using the forecasting method of artificial neural networks after that doing a comparison of inventory control calculations using the min-max stock method with company policy. The results showed that the comparison of the cost of supplying 1 kg of Beras Konyaku using the min-max stock method of IDR 221,171,437 was more optimal than the company policy that was applied, IDR 240,465,522. The min-max stock method states that the existence of safety stock means adding stock to the warehouse and the presence of storage costs for safety stock does not affect the increase in control inventory costs from before, but a decrease in inventory costs. So, the min-max stock method is the optimal method in determining the maximum and minimum par levels that will avoid or minimize stockouts in stores so that optimal inventory control is carried out